Investigation of the structure and sorption peculiarities of cobalt and uranium ions by nanocomposites based on montmorillonite and tetraethoxysilane - Doroshenko, Dmytro; Pylypenko, Igor; Kovalchuk, Iryna; Kornilovych, Borys; Spasonova, Larysa (Eastern-European Journal of Enterprise Technologies, 2018)
The structure and adsorption characteristics of silica -and montmorillonite-based nanocomposites are investigated. Tetraethoxysilane was used as a source of silica. The porous structure was investigated by the method of low-temperature nitrogen adsorption. According to the research results, it was found that a small amount of silica in nanocomposite samples (14 % SiO2) contributes to the formation of material with a larger specific surface area and greater number of meso- and macropores compared to original montmorillonite. This, in turn, leads to a better diffusion of ions of different nature into the nanocomposite structure. An increase in the silica content (up to 57 % SiO2) allows obtaining microporous samples with a large specific surface area. It was determined that the increase of the montmorillonite content in the investigated samples contributes to the improvement of the adsorption properties of nanocomposites in relation to the removal of cobalt(II) ions from the aqueous medium. At an optimum silica content (3–14 % SiO2), the experimental samples retain high values of maximum cobalt adsorption (14 mg/g), as well as original montmorillonite. It was also found that an increase in the silica concentration in the samples increases the efficiency of removal of uranium(VI) ions from the aqueous medium (from 12 mg/g in original montmorillonite to 25 mg/g for nanocomposites with a silica content of 57 %). This is due to, first, an increase in the specific surface area of the samples, and secondly – an increase in the number of surface hydroxyl groups, which more selectively remove uranium from solutions. Thus, selection of the chemical composition of nanocomposites based on silica gel and montmorillonite allows regulating porous structures and surface chemistry, and thus increasing the sorbent efficiency depending on the task